Antifouling sulfonated polyamide nanofiltration hollow fiber membrane prepared with mixed diamine monomers of BDSA and PIP. Issue 89 (15th December 2017) - Huang, Ben-Qing; Xu, Zhen-Liang; Ding, Hao; Miao, Ming-Che; Tang, Yong-Jian
Abstract : A novel high-flux sulfonated polyamide nanofiltration (NF) hollow fiber membrane was made from the mixed monomers of 2, 2′-benzidinedisulfonic acid (BDSA) and piperazine (PIP). Abstract : A novel high-flux sulfonated polyamide nanofiltration (NF) hollow fiber membrane was made from the mixed monomers of 2, 2′-benzidinedisulfonic acid (BDSA) and piperazine (PIP). By optimizing the preparation parameters (TMC concentration, reaction time and BDSA/PIP mixing ratio), the optimized NF membrane possessed a pure water permeability (PWP) of 49.1 L m −2 h −1 and a Na2 SO4 rejection of 95.5% under 4 bar. The molecular weight cut off (MWCO) of the BDSA/PIP NF membrane was about 400 Da. Furthermore, in a long-term antifouling test with 0.3 g L −1 bovine serum albumin (BSA) solution, the total flux decline rate (FDR) and the flux recovery ratio (FRR) of the membrane were 16.7% and 85.7% respectively, which indicated the good antifouling properties and application prospects of the TFC NF membrane.